2006
DOI: 10.1093/intqhc/mzi109
|View full text |Cite
|
Sign up to set email alerts
|

One plunge or two?—hand disinfection with alcohol gel

Abstract: Doubling the volume of alcohol gel used for hand disinfection significantly improves the efficiency of coverage of the hands with alcohol gel. This may result in lower bacterial count on the hands and may reduce the spread of nosocomial infections including that of methicillin-resistant Staphylococcus aureus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…As shown in Tables 1 , 2 and 3 , this included two parallel design [ 16 , 17 ], one crossover [ 18 ] and eight within-subject [ 19 26 ] RCTs, and one parallel design [ 27 ], one crossover [ 28 ] and seven within-subject [ 29 35 ] NRTs. Apart from one study [ 17 ] conducted in China, all included evidence derives from high income countries, including Australia (n = 1) [ 28 ], Austria (n = 2) [ 25 , 33 ], France (n = 1) [ 31 ], Germany (n = 3) [ 16 , 18 , 32 ], Switzerland (n = 5) [ 23 , 24 , 26 , 29 , 30 ], UK (n = 3) [ 27 , 34 , 35 ] and USA (n = 2) [ 19 , 22 ], while two were multisite studies conducted in the Netherlands and UK [ 21 ], and in Germany and USA [ 20 ]. Despite searching for studies published since 1980, the publication year of the included studies ranged from 2003 to 2020, with most studies (n = 15) published within the last 10 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Tables 1 , 2 and 3 , this included two parallel design [ 16 , 17 ], one crossover [ 18 ] and eight within-subject [ 19 26 ] RCTs, and one parallel design [ 27 ], one crossover [ 28 ] and seven within-subject [ 29 35 ] NRTs. Apart from one study [ 17 ] conducted in China, all included evidence derives from high income countries, including Australia (n = 1) [ 28 ], Austria (n = 2) [ 25 , 33 ], France (n = 1) [ 31 ], Germany (n = 3) [ 16 , 18 , 32 ], Switzerland (n = 5) [ 23 , 24 , 26 , 29 , 30 ], UK (n = 3) [ 27 , 34 , 35 ] and USA (n = 2) [ 19 , 22 ], while two were multisite studies conducted in the Netherlands and UK [ 21 ], and in Germany and USA [ 20 ]. Despite searching for studies published since 1980, the publication year of the included studies ranged from 2003 to 2020, with most studies (n = 15) published within the last 10 years.…”
Section: Resultsmentioning
confidence: 99%
“…Despite searching for studies published since 1980, the publication year of the included studies ranged from 2003 to 2020, with most studies (n = 15) published within the last 10 years. Furthermore, most studies (n = 15) were conducted in laboratory settings [ 19 26 , 29 35 ], while five studies were based in a healthcare setting [ 16 18 , 27 , 28 ]. The study participants were HCWs [ 16 18 , 21 , 23 , 24 , 26 29 , 31 ], and non-HCWs [ 20 ], while in eight laboratory-based studies participants were described as volunteers [ 19 , 22 , 25 , 30 , 32 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Using education can improve compliance 28,29 Doubling the amount of alcohol gel hand disinfectant used can result in improved surface area and lower bacterial count on caregiver hands 30 Early mobilization/early exercise Ambulation of mechanically ventilated patients to reduce length of stay 31 Individually tailored exercise training can improve muscle force at discharge 32 Whole-body rehabilitation can decrease delirium duration and result in better functional outcomes 33 Central venous catheter blood stream infection Insertion and maintenance bundles, which include training (operator and assistant), removal as soon as feasible, hand hygiene, daily dressing inspection with changes occurring when soiled, and discouragement of catheter changes over guide wires and blood sampling 34 Sequential infection control education and performance feedback 35,36 Use of maximal barrier protection [37][38][39] Use of sutureless securement device 40 Evaluate new innovations prior to use; mechanical valves may increase infection rate [40][41][42] (continued on next page)…”
Section: Cautismentioning
confidence: 99%
“…7 Some healthcare personnel believe that the amount delivered by some dispensers is excessive and takes too long to dry, and as a result, they apply doses lower than those recommended. 2,5,8 This issue is of concern since it has been suggested that application of small amounts of ABHR may not be sufficient to cover all surfaces of the hands and reduce bacteria on hands to the degree recommended by regulatory agencies. [9][10][11][12] We sought to identify the volume of ABHR preferred for use by nurses.…”
Section: Introductionmentioning
confidence: 99%